(untitled) (Journal of Environmental Science and Natural Resources, 2016)
Biogas is one of the most eco-friendly alternative renewable energy sources, to meet future energy requirement. In order to carry out this research, two experiments were set up taking cow dung, cow dung with wasted flour and cultured Bacteria with waste flour. In Experiment 1, only cow dung was used in build biogas plant and decomposed periodically for 28 days. After that cow dung slurry (as inoculum) with waste flour were decomposed for 28 days. In Experiment 2, same waste flour with cultured anaerobic bacterial colony (as inoculum) was used as the feed stocks and the experiment was completed in 28 days. Result of the Study revealed that production of biogas was higher and consuming less time when cultured bacterial colony was used as inoculum with feed stock, compared to that of cow dung. In this experiment, garbage is decomposed with approximately all type of anaerobic bacteria. If methanogens, facultative anaerobes and other bacteria which are responsible for anaerobic digestion and biogas formation, are separately cultured and these garbages are separately decomposed with this bacteria. Anaerobic decomposition has a number of environmental benefits including production of green energy and natural fertilizers. The process of converting organic feed stock into biogas can serve as a substitute for fossil fuels and artificial fertilizers, reducing the amount of greenhouse gases released into the atmosphere. J. Environ. Sci. & Natural Resources, 8(2): 33-36 2015